Capacity of ICT’s to virtualize field work: Theory and practice from geography - García-Comendador, Julián; Fortesa, Josep; Ruíz Pérez, Maurici; Estrany, Joan; Sastre Canals, Bartomeu; Petrus Bey, Joana Maria (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Geographical didactics in higher education incorporates field work as a first order instrument. Field trips constitute the basis of geographical research since they provide knowledge about the configurative elements and processes of the geographical space. Geotechnologies can virtually recreate scenarios analogous to traditional field trips. The qualifications of two groups of students were compared without finding significant differences between those who made virtual and traditional field trips. The virtualization of field trips is a useful and inclusive element beyond the pandemic context.